Modeling and Simulation of a Vector-Controlled Synchronous Machine in Motoring and Generating Mode - Losic, Novica A. (2007)
A vector-controlled permanent-magnet (PM) synchronous machines has been modeled and simulated in both the monitoring and generating mode of operation. The control provides for the maximized torque and, therefore, maximum efficiency during motoring, and for a controlled power, tight voltaje regulation in the presence of load changes, and minimum bus voltaje ripple at the output of ac-dc converter during generation. A three phase-locked loop is used to provide the unity vector information in both the sensor-based and sensorless scheme. The results of the simulation are presented, including modeling details and simulation parameters.